Canadian Consensus Conference on the Management of Viral Hepatitis - Association for Study of the Liver (CASL) Consensus Conference Rapporteur Group (Canadian Journal of Gastroenterology)
These proceedings of a consensus conference on the management of viral hepatitis were sponsored by the Canadian Association for Study of the Liver (CASL) and Health Canada. Experts in various aspects of viral hepatitis presented a review of the medical literature on assigned topics. Three expert panels were convened; they debated assigned topics, which corresponded to the reviews presented earlier. Attempts were made to reach consensus on a number of recommendations about the management of viral hepatitis. The content of the literature reviews, the debates and consensus statements were synthesized into a preliminary document. The report gives some background and offers recommendations aimed at both the general practitioner and the specialist.